Impact of Smoking on Macrophage‐Related Chemokines During Initial Peri‐Implantitis: A Prospective Cohort Study - Buyukakcali Altay; Buse Naz; Turgut Cankaya, Zeynep; Yilmaz, Mustafa; Gürsoy, Mervi; Bodur, Aysen; Gürsoy, Ulvi Kahraman (Wiley, 2025)
Objectives: Smoking disrupts macrophage chemokine response and delays healing. This study aims to investigate the effect of smoking on peri-implant crevicular fluid (PICF) levels of macrophage-related chemokines, C-C motif chemokine ligand 2 (CCL-2), C-C motif chemokine ligand 8 (CCL-8), C-X-C motif chemokine ligand 9 (CXCL-9), and C-C motif ligand 3 (CCL-3), before and after non-surgical treatment of initial peri-implantitis.
Methods: Fifty-five implants (27 non-smoking [NSPI] and 28 smoking [SPI]) with initial peri-implantitis (bleeding on probing [BOP+], probing pocket depth [PPD] of 6–7 mm) were included in the study. Clinical parameters were recorded, and PICF samples were collected before and 4 months after non-surgical treatment. PICF concentrations of CCL-2, CCL-8, CCL-3, and CXCL-9 were measured with Luminex assay. The Mann–Whitney U-test, Wilcoxon signed-rank test, and repeated measures analysis of variance test were used to analyze differences between and within the groups.
Results: Baseline CCL-2 (p < 0.001) and CXCL-9 (p = 0.026) levels (pg/30 s) were significantly lower in smokers compared to non-smokers, while no difference was observed for CCL-3 between the two groups (p = 0.320). Only CCL-2 levels (pg/30 s) decreased in the NSPI group in response to non-surgical treatment (p = 0.037).
Conclusion: Smoking disturbs the expressions of macrophage-related chemokines in the early phase of peri-implantitis. These findings may indicate the impaired control of infection during initial peri-implantitis and explain the accelerated progression of the disease in smokers. This study was not registered prior to participant recruitment.
Trial Registration: https://clinicaltrials.gov/study/NCT06810401.